Auditor's Professional Skepticism: An Empirical Study At Public Accounting Firm In Central Java Province - Ardiani Ika Sulistyawati,; Aprih Santoso, (Jurnal Akuntansi, 2021)
This study examines and analyzes the effect of experience, expertise, audit situation, ethics, and legal certainty on auditors' professional skepticism. The sample of this research is auditors who work at a public accounting firm in Central Java Province. Samples were taken using the non-probability sampling method, using the purposive sampling technique with 104 auditors as respondents. The analysis method used is PLS analysis. The research results show that experience and ethics affect the professional skepticism of auditors, while expertise, audit situation, and legal certainty do not affect the professional skepticism of auditors. The results of this study are expected to maintain the professional skepticism of auditors in evaluating critical audit evidence.